Pengaruh Cita Rasa dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Es Teh Tali Pinggir - Faris Albaniya; Netti Nurlenawati; Dexi Triadinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Es Teh Tali Pinggir is a beverage business that is quite popular with many people, because the price is affordable and refreshing when drunk. This business venture already has many branches, one of which is located in Teluk Jambe Karawang. The aim of this research is to understand the influence of taste and service quality on customer satisfaction. The analytical method used includes a quantitative approach. The target sample is customers who are buying products from Es Teh Tali Pinggir. The samples collected were 96 people and the samples were determined using the lemeshow sampling technique. The data collection technique for this research is to use questionnaire data collection which is filled out by Es Teh Tali Pinggir customers. Based on research findings, research on taste has a positive and significant influence on customer satisfaction, while research on service quality also has a positive and significant influence. In addition, research on the combined influence of taste and service quality has been proven to have a positive and significant impact on customer satisfaction. This research shows that customer satisfaction with Es Teh Tali Pinggir is more influenced by taste.